Aplicação do indicador de eficiência global de equipamento no setor de chaparia de uma indústria metalúrgica - Santos, Lucas Cordeiro dos (2022)
The period of the COVID-19 pandemic brought several challenges for companies, which saw their supply chains strangled as they tried to satisfy the needs of now increasingly demanding customers in terms of lead time and quality. In this context, where inefficiency can be decisive for success or failure, the present study finds a scenario of difficulties in a company, which turns to Lean philosophy as a way to guarantee improvements in the efficiency of its processes, and the present study takes forward in its initiatives. This paper presents an application of the overall equipment effectiveness indicator in the Platework Sector of a Metallurgical Industry with a goal of identifying potential improvement points for the productive process. Within a period of three months, production related data was collected by a system developed by the author, and the methodology for calculating the OEE indicator was applied. The result of the analysis produced OEE values ranging from 58% to 70% between the analyzed months, with subsequent analysis of availability, performance, and quality. Finally, an action plan was structured with a special focus on performance points, which are extremely related to the lack of preventive maintenance for the equipment in the sector.